2002
DOI: 10.1006/jcat.2002.3555
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Vanadium Phosphate Catalysts Prepared Using Precipitation with Supercritical CO2 as an Antisolvent

Abstract: A new preparative route for vanadium phosphate catalysts is described using supercritical CO2 as an antisolvent. The amorphous microspheroidal VPO produced is shown to be more active than comparable crystalline VPO catalysts for the selective oxidation of n-butane to maleic anhydride and, furthermore, does not require an extensive pre-treatment or activation period to establish full catalytic activity. VPO catalysts prepared using supercritical CO2 as an antisolvent maintain their amorphous nature throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 45 publications
2
66
0
Order By: Relevance
“…Interestingly, and in total contrast to vanadium phosphates prepared using the VPO and VPD methods, 25 the sc-VPO material did not require any reaction time to become active, 31 whereas the VPO and VPD typically require several hours under reaction conditions before they reach their optimal activity. 25,31 Examination of the scCO 2 -VPO material by electron microscopy showed that both the fresh and used catalysts comprised spheroidal particles (Fig. 8) that are not changed on exposure to the reaction gases.…”
Section: 52mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, and in total contrast to vanadium phosphates prepared using the VPO and VPD methods, 25 the sc-VPO material did not require any reaction time to become active, 31 whereas the VPO and VPD typically require several hours under reaction conditions before they reach their optimal activity. 25,31 Examination of the scCO 2 -VPO material by electron microscopy showed that both the fresh and used catalysts comprised spheroidal particles (Fig. 8) that are not changed on exposure to the reaction gases.…”
Section: 52mentioning
confidence: 99%
“…31,55 The use of scCO 2 as an anti-solvent for the controlled precipitation of materials from conventional solvents has been widely applied to the production of a range of materials. These include polymers, pharmaceutical chemicals, explosives, superconductors, and catalysts.…”
Section: 52mentioning
confidence: 99%
See 1 more Smart Citation
“…An adsorbate-type structure of the active site allowing dynamical response will be useful whereas a closely packed 3-D crystalline state will hinder such a process with high activation barriers. Such ''adsorbatelike'' active phases [77,78] can be identified with probe molecule reactions [79][80][81][82][83][84][85][86] and have been rationalized for covering some bulk catalysts [13,42,[87][88][89][90][91] as consequence of surface energy minimization.…”
Section: Size and Functions Of Active Sitesmentioning
confidence: 99%
“…For the oxidation of n-butane to maleic anhydride the technical catalyst is vanadium-phosphorusoxide (VPO) [5,6], representing a complex material being composed of a variety of phases [7][8][9]. Some experimental results suggest that in VPO the structure of the catalytically active species is only weakly related to the average bulk structure [10,11].…”
Section: Introductionmentioning
confidence: 99%